Radiographic Study of Distal Radius Parameters in Patients Visiting Tertiary Care Hospital - Shrestha, S.; Mansur, D. I.; Shrestha, R.; Karki, S.; Maskey, S.; Malla, M.; Basi, A.; Khadka, S. K. (Kathmandu University Medical Journal, 2022)
Background The important morphological parameters of distal radius namely palmar tilt, radial inclination, radial height and ulnar variance are consequential in the evaluation and management of the distal radius fracture, distal radius plate design and kinesiology. Correction of these parameters in anatomical alignment is important to restore the normal biomechanics of the wrist joint. Objective To ascertain the distal radius parameters in the patients attending tertiary care hospital with regard to gender and age. Method The wrist radiographs (postero-anterior and lateral views) of 125 patients, from 16 to above 60 years of age were used to determine the four parameters of distal radius. The subjects were divided into gender and three different age groups (16-36 years, 37-57 years and > 57 years). Independent t-test and ANOVA test was used for statistical analysis with level of significance set at p ≤ 0.05. Result The mean palmar tilt was 15.69 ± 4.84° (p-value = 0.40). The mean radial inclination was 22.58 ± 2.82° (p-value = 0.88). The mean value of radial height was 10.31 ± 1.59 mm (p-value= 0.001). Positive ulnar variance were recorded in maximum of subjects (46.40%) and the least was neutral (16.80%). Conclusion The distal radius parameters of our population were similar to the Orthopedic Trauma Association standard reference value. And there was significant difference in radial height between males and females.